Along-the-channel modeling and analysis of PEFCs at low stoichiometry: Development of a 1+2D model. (5th December 2019) - Pant, Lalit M.; Gerhardt, Michael R.; Macauley, Natalia; Mukundan, Rangachary; Borup, Rodney L.; Weber, Adam Z.
Abstract: Water management remains a key challenge in polymer-electrolyte fuel cells. In this work, a pseudo 3-D (1+2D) model is developed to account better for changes of water management along the channel, as well as verify the possibilities of using differential cells for data capture and translation to integral cell performance. An accurate 2-D membrane-electrode-assembly model is developed for differential cell modeling, which is combined with an along-the-channel stepping algorithm to account for down the channel changes in pressure, temperature, reactant concentration, and relative humidity. Variations in cell performance along the channel due to changes in operating conditions are characterized quantitatively and optimized, where drier feed conditions demonstratively require such an approach. Overall, the study identifies gaps between differential and integral cells including those related to flow velocity and highlights the need for better models to understand and link integral cell performance and water management.